Collective Bargaining in Sport: Challenges and Benefits - Daniel Pannett (UCL Journal of Law and Jurisprudence, 2015)
This article analyses the relationship between sport law and employment law – in particular, the legal recognition and involvement of collective bargaining in professional sport. Drawing on a number of specific examples – professional rugby, Formula One motor racing and mixed martial arts – this article attempts to identify existing and possible future challenges for the applicability of collective bargaining in this unusual legal context. Section B sets out the general advantages of collective bargaining in a sporting context, then explores the applicable legal structures and characteristics present in professional sport in more detail. Section C examines these characteristics in the specific context of professional rugby, motor racing and mixed martial arts. Finally, Section D examines both systemic and specific legal issues that may arise if and when collective influence grows in the professional sporting employment relations. The conclusion of this article, Section E, is that, whilst collective bargaining presents a number of challenges to the law of professional sport, these challenges can (and should) be overcome. >> Read full article